Higher mortality rate in postoperative icu patients is associated with combination of early enteral and parenteral nutrition. - Liem, Raymond; Taslim, Nurpudji Astuti (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: This study aims to examine the impact of early nutrition on mortality in postoperative ICU patients. The study also seeks to explore the impact of early nutrition on other clinical outcomes. Methods: This retrospective observational study included 361 postoperative ICU patients and divided by four groups based on their early nutritional support (early enteral, early parenteral, early mixed enteral and parenteral, and no early nutrition). Baseline characteristics, nutritional intake was assessed using 24hours food recall, length of stay in ICU, hospital LOS, duration of mechanical ventilation, and mortality were evaluated. Statistical analyses included univariate and multivariate models to assess the relationship between early nutrition and clinical outcomes. Result: The early PN and EN & PN groups had higher ICU mortality rates (33.6% and 26.5%, respectively) compared to the EN group (19.1%) and no early nutrition group (11.1%). Early PN was associated with an increased odds ratio for mortality (OR = 3.03, 95% CI = 0.83, 11.09). The EN & PN group also showed increased odds (OR = 4.82, 95% CI = 1.10, 21.11). The highest median calorie intake was in the PN group, while the longest ICU LOS was in the EN & PN group. Conclusion: Early supplemental parenteral nutrition, particularly when combined with enteral nutrition, is associated with higher mortality in postoperative ICU patients. Early enteral nutrition appears to be a safer option, and careful consideration should be given to the risks and benefits of different nutritional interventions in this patient population.